Nursing in Australian general practice: directions and perspectives - Halcomb, E.; Davidson, Patricia; Daly, J.; Griffiths, R.; Tofler, G.; Yallop, E. (Australasian Medical Publishing Company Pty Ltd, 2005)
Primary health care services, such as general practices, are the first point of contact for many Australian Health care consumers. Until recently, the role of nursing in Australian primary care was poorly defined and described in the literature. Changes in policy and funding have given rise to an expansion of the nursing role in primary care. This paper provides a review of the literature and seeks to identify the barriers and facilitators to implementation of the practice nurse role in Australia and identifies strategic directions for future research and policy development.